Economic burden of primary compared with recurrent Clostridium difficile infection in hospitalized patients: a prospective cohort study. Issue 3 (July 2016) - Shah, D.N.; Aitken, S.L.; Barragan, L.F.; Bozorgui, S.; Goddu, S.; Navarro, M.E.; Xie, Y.; DuPont, H.L.; Garey, K.W.
Summary: Background: Few studies have investigated the additional healthcare costs of recurrent C. difficile infection (CDI). Aim: To quantify inpatient treatment costs for CDI and length of stay among hospitalized patients with primary CDI only, compared with CDI patients who experienced recurrent CDI. Methods: This was a prospective, observational cohort study of hospitalized adult patients with primary CDI followed for three months to assess for recurrent CDI episodes. Total and CDI-attributable hospital length of stay (LOS) and hospitalization costs were compared among patients who did or did not experience at least one recurrent CDI episode. Findings: In all, 540 hospitalized patients aged 62 ± 17 years (42% males) with primary CDI were enrolled, of whom 95 patients (18%) experienced 101 recurrent CDI episodes. CDI-attributable median (interquartile range) LOS and costs (in US) increased from 7 (4–13) days and 13, 168 (7, 525–24, 456) for patients with primary CDI only versus 15 (8–25) days and 28, 218 (15, 050–47, 030) for patients with recurrent CDI ( P < 0.0001, each). Total hospital median LOS and costs increased from 11 (6–22) days and 20, 693 (11, 287–41, 386) for patients with primary CDI only versus 24 (11–48) days and 45, 148 (20, 693–82, 772) for patients with recurrent CDI ( P < 0.0001, each). The median cost of pharmacological treatment while hospitalized was 60 (23–200) for patients with primary CDI only ( N = 445) and 140 (30–260) for patients with recurrent CDI ( P = 0.0013). Conclusion: This study demonstrated that patients with CDI experience a significant healthcare economic burden attributed to CDI. Economic costs and healthcare burden increased significantly for patients with recurrent CDI.